1971
DOI: 10.1161/01.cir.44.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiac Contractility

Abstract: SUMMARYIt was considered that the relationship between dp/dt and simultaneously developed pressure during the course of isovolumic contraction might afford a more accurate measure of contractility than the maximum rate of intraventricular pressure rise (peak dp/dt). In six cat papillary muscles contracting isometrically from any given preload, the ratio of the rate of tension development (dT/dt) to simultaneously occurring isometric tension always varied directly with the contractile state. This ratio rose sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
3

Year Published

1975
1975
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(28 citation statements)
references
References 29 publications
2
23
0
3
Order By: Relevance
“…The LaPlace relation defines force in a hollow body as the product of pressure and radius squared, and has been used by numerous investigators to determine the tension in the ventricular wall (13)(14)(15)(16)(17)(18)(19). Hefner et al demonstrated that this arch measured this product of pressure and radius squared, and subsequent studies by Newman and Walton (10,20,21) have demonstrated (2)(3)(4)10). that values obtained with this arch corresponded with calculated values of wall force, being influenced by changes in ventricular size and/or pressure.…”
Section: Selecting ( D P / D T ) / Kmentioning
confidence: 99%
See 2 more Smart Citations
“…The LaPlace relation defines force in a hollow body as the product of pressure and radius squared, and has been used by numerous investigators to determine the tension in the ventricular wall (13)(14)(15)(16)(17)(18)(19). Hefner et al demonstrated that this arch measured this product of pressure and radius squared, and subsequent studies by Newman and Walton (10,20,21) have demonstrated (2)(3)(4)10). that values obtained with this arch corresponded with calculated values of wall force, being influenced by changes in ventricular size and/or pressure.…”
Section: Selecting ( D P / D T ) / Kmentioning
confidence: 99%
“…From the data in Table I1 there appears to be no significant change in this index with changes in preload. However, there is a great deal of variation (1,2,10).…”
Section: Selecting ( D P / D T ) / Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is more appropriate to formulate an LV contractility index on the basis of LV wall stress (5,9,24). Numerous methods have been devised to measure LV wall stress (13) or to approximate it by use of geometric models (8,19,36). Measurement of transmural wall stress (with implantable strain gauges) is hampered, however, by the degree of coupling between the transducer and the ventricular wall (5).…”
mentioning
confidence: 99%
“…A great deal of effort has been made to assess their specificity and prediction capability (Mason et al, 1971;Peterson et al, 1974;Lambert et al, 1983;Kass et al, 1987;Kass and Beyer, 1993). Most studies have indicated the peak of the first time derivative of the ventricular pressure dP/dt max to be the most sensitive cardiac index of inotropic changes (Kass et al, 1987).…”
Section: Introductionmentioning
confidence: 99%